ANALYSIS OF EFFECT NON FINANCIAL MEASURES DISCLOSURE, CORPORATE GOVERNANCE, INTELLECTUAL CAPITAL AND AUDIT QUALITY TO COMPANY PERFORMANCE - Dedi Putra; Lusi Indriyana (Proceeding International Conference on Information Technology and Business, 2018)
The objective of this research was to prove empirically the effect of the nonfinancial measures disclosure, the corporate governance, the intellectual capital, and the audit quality on the corporate performance of banking companies indexed in Indonesian Stock Exchange in the period of 2014-2016. The type of this research was the quantitative research. The independent variables of this research were the non-financial measures disclosure, the corporate governance, the intellectual capital, and the audit quality. The dependent variable of this research was the company performance (CAR). This research used the purposive sampling technique. The number of samples of this research was 111 banking companies indexed in the period of 2014-2016. The type of this research data was the secondary data. The data collecting technique used in this research was documentation. The data analysis technique used in this research was the multiple linear regression by using IBM SPSS Version 21 program. The result of this research showed that the non-financial measures disclosure had an effect on the company performance; while, the corporate governance, the intellectual capital, and the audit quality did not affect the company performance. Keywords: Non Financial Measures Disclosure, Corporate Governance, Intellectual Capital, Audit Quality, Capital Adequacy Ratio (CAR)